Manajemen Pengawasan Fungsional dalam Penggunaan Smart Auditing di Inspektorat Daerah Kota Makassar - Dariesta, Theresia Jasmine; Rahmat, Dadang; Buchori, Rega Imam; Margaretha, Tiur; Darmawan, Ivan (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Functional supervision is one part of government administration that cannot be separated, in order to monitor and also make improvements to things that deviate from the rules. One of the functional supervisions in Makassar City through the Makassar City Regional Inspectorate is the use of smart auditing as a form of technology implementation within the scope of the Electronic-Based Government System (SPBE) at the Makassar City Regional Inspectorate. Smart auditing is one of the systems used to effectively check SPJ from Makassar City SKPDs through an online system so that it can be done quickly regardless of time and place. The writing of this research uses descriptive qualitative methods using secondary data as a comprehensive data source for this scientific writing.